EVALUASI KINERJA PROGRAM STUDI MENGGUNAKAN METODE INTEGRATED PERFORMANCE MEASUREMENT SYSTEMS DAN ANALYTIC HIERARCHY PROCESS (Studi kasus : Program Studi Teknik Informatika Universitas Hasyim Asy’ari) - Mashuri, Chamdan; Faizah, Arbiati (Inovate, 2019)
Implementing performance improvement programs, studios are solutions that can be used to achieve betterHasyim Asy'ari University. Using the Integrated Performance Measurement Systems (IPMS) andAnalitycal Hierarchy Process (AHP) methods, studio performance appraisal programs can be carried outoptimally because this method is all the needs and needs of all stakeholders that will be needed to make aneed to make the Main Performance Indicator (KPI). While AHP is used in making decisions from eachKPI to be weighted and then assessed to determine the scores of the studio program. The results obtainedfrom this study are in the results of the evaluation of informatics engineering courses obtained 9 generalcriteria and 28 sub-criteria or KPI. The average rating system from KPI is 81.53% giving informationabout the performance of the Unhasy Informatics Engineering Study Program as a whole its performancehas been good. For the KPI, the average time to successfully get a job and the dictate ratio of the subject isthe highest score while the KPI ratio of AC to the lecture room gets the lowest score.Keywords: Performance measurement, Integrated Performance Measurement System (IPMS), AHP.